Psycho-Islamic principles of retaining information in human memory: a conceptual study - Badi, Jamal Ahmed Bashier; Solihu, Abdul Kabir Hussain; Dzulkifli, Mariam Adawiah; Abdul Rahman, Abdul Wahab; Olorogun, Lukman Ayinde (2015)
Human brain is responsible for much of human activities such as reasoning, planning, speaking, movement, emotions, as well as problem solving. Understanding the mechanism that governs how the brain works is a research that now entails multidisciplinary approach. Though other primates do store and recall data, human brain processes information in a unique way. The modes of retaining and executing information in human brain are categorised into Short Term Memory, otherwise known as Working Memory, and Long Term Memory. The Qur’an is the only book that is most committed into memory by many people generations after generations for over 1400 years, regardless of age, gender, and ethnicity. Thus we have chosen the Qur’an and Huffaz (memorisers of the Qur’an) as the measurements of our study. We come up with a special model of the Qur’anic memorisation. We examine the role of human brain in sustaining the memorisation for long time which can easily be retrieved whenever the need arises. Keyword: Human brain, human memory, Qur’anic memorisation, huffaz